2011
DOI: 10.1093/ntr/ntr153
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20 Shows Linkage With DSM-IV Nicotine Dependence in Finnish Adult Smokers

Abstract: Introduction: Chromosome 20 has previously been associated with nicotine dependence (ND) and smoking cessation. Our aim was to replicate and extend these findings.Methods: First, a total of 759 subjects belonging to 206 Finnish families were genotyped with 18 microsatellite markers residing on chromosome 20, in order to replicate previous linkage findings. Then, the replication data were combined to an existing wholegenome linkage data resulting in a total of 1,302 genotyped subjects from 357 families. ND diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Genome-wide significant linkage signals have been observed in the chromosome 20q13 region containing CHRNA4 for maximum number of cigarettes smoked in a 24-h period 74 and in the nearby chromosome 20q11 region for DSM-IV-defined nicotine dependence. 75 Several candidate gene association studies have focused on CHRNA4 . 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 Among the common SNPs with reported associations, only rs2236196 was associated in our study ( P =0.027, Table 3 ): its minor allele (frequency=0.28) conferring increased risk for nicotine dependence, consistent with prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide significant linkage signals have been observed in the chromosome 20q13 region containing CHRNA4 for maximum number of cigarettes smoked in a 24-h period 74 and in the nearby chromosome 20q11 region for DSM-IV-defined nicotine dependence. 75 Several candidate gene association studies have focused on CHRNA4 . 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 Among the common SNPs with reported associations, only rs2236196 was associated in our study ( P =0.027, Table 3 ): its minor allele (frequency=0.28) conferring increased risk for nicotine dependence, consistent with prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…NNAT is one of the genes located in this region. Although this study [53] did not specifically assess polymorphisms in the NNAT gene, our data show that Nnat is potentially involved in driving the linkage of this chromosomal region with nicotine dependence (i.e., at least in women).…”
Section: Discussionmentioning
confidence: 80%
“…Developmentally regulated, Nnat is highly expressed during neurogenesis [70] , and it may influence site-specific synaptic events such as long-term potentiation or depression by modulating local dendritic calcium levels [71] . Perhaps most importantly, a recent genetic linkage study, using DSM-IV criteria, identified chromosome 20q11.23 as a locus harboring genetic variations linked to nicotine dependence [53] . NNAT is one of the genes located in this region.…”
Section: Discussionmentioning
confidence: 99%